A Take-Off from the Land. Agriculture and Social Networks in the Making of Kvänum as an Industrial District, 1930-2007 - Nyström, Lars (TSEG - The Low Countries Journal of Social and Economic History, 2016)
During the 1930s the previously predominantly agrarian Kvänum area in Western Sweden started to industrialize. Initially most of the emerging enterprises specialized in farm machinery, especially harvest handling equipment such as straw fans, straw choppers and hot air dryers. Production later diverged into a number of branches. This article discusses the making of Kvänum as an industrial district as a multifold process of interaction between agriculture and industry. It also addresses industrialisation from the point of view of social networks. Contrasting the predominant view on the role of trust and cooperation as main engines of cluster dynamics, the results from Kvänum stresses the importance of involuntary sharing of information, under a situation of fierce, cutting edge competition.